PERAN MASYARAKAT DALAM MENEKAN LAJU PEMBERANTASAN COVID-19 DI KABUPATEN TANAH DATAR - Fadjri Wahyu; Dian Flora; Desni Yulinda; Tri Yuliani; Iswadi Iswadi; Irwandi Irwandi; Novi Budiman; Beni Putra Hanafi; Riki Rikarno (IAIN Batusangkar, 2020)
The spread of covid-19 is a global disaster and worldwide, including in the small area of Tanah Datar Regency. The spread of positive cases in Tanah Datar district is currently increasing rapidly. The government is trying to suppress the growth rate but it does not produce maximum results. This research uses descriptive method with analysis through literature study through various kinds of new theories and journals. This research proves that there must be community collaboration with the government in the sense that the community should take a role in eradicating the Covid-19 case with the aim that the programs that have been planned by the government can run optimally and produce good achievements and be able to reduce the growth rate of the spread of the Covid-19 outbreak.